The Difficulty of Finding Halal Food for Muslim Minorities: Analysis of Maqashid Shariah - Yusuf, Nasruddin; Sarib, Suprijati; Evra, Willya (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This article explores the challenges of Manado's Muslim minorities in finding halal food from the perspective of maqashid Sharia. As a Muslim minority area, food vendors and production in Manado dominate with non-Muslim and non-halal food vendors. It is difficult for minority Muslim communities to practice religious principles, especially eating halal food. The method used in this study is qualitative with normative juridical and empirical approaches. Data obtained through in-depth interviews with research informants from 29 Muslim communities were analyzed inductively. The results found that minority Muslim communities in Manado face significant challenges in finding halal food, given the dominance of non-halal food in their neighborhood. However, personal decisions to choose halal food reflect their loyalty to religious teachings (hifdz al-din), concern for personal health (hifdz al-nafs), and wise asset management (hifdz al-mal). There is clear evidence that the principles of maqashid Sharia are essential in guiding individual actions in facing the challenges of daily life. In this context, religious beliefs are the primary guide for Manado's Muslim community in living their lives and maintaining the integrity of Islamic values in their decisions regarding food.